Severe Reactions to DTP Vaccine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Severe reactions experienced by 60 children within 48 hours of DTP immunization were reported from the UCLA School of Medicine, Los Angeles, CA.